Stages Of Drawing Up A Mathematical Model Of The Economic Issue - Gulhayo Komolova Shukirillayevna (Euro Asian Journal Publishing, 2024)
The article presents the concept of a mathematical model and the stages of drawing up a mathematical model of an economic issue.
Keywords: Economy; mathematical model; sequence